First-in-Human Randomized Study to Assess the Safety and Immunogenicity of an Investigational Respiratory Syncytial Virus (RSV) Vaccine Based on Chimpanzee-Adenovirus-155 Viral Vector–Expressing RSV Fusion, Nucleocapsid, and Antitermination Viral Proteins in Healthy Adults. (24th July 2019) - Cicconi, Paola; Jones, Claire; Sarkar, Esha; Silva-Reyes, Laura; Klenerman, Paul; de Lara, Catherine; Hutchings, Claire; Moris, Philippe; Janssens, Michel; Fissette, Laurence A; Picciolato, Marta; Leach, Amanda; et al.
Abstract: Background: Respiratory syncytial virus (RSV) disease is a major cause of infant morbidity and mortality. This Phase I, randomized, observer-blind, placebo- and active-controlled study evaluated an investigational vaccine against RSV (ChAd155-RSV) using the viral vector chimpanzee-adenovirus-155, encoding RSV fusion (F), nucleocapsid, and transcription antitermination proteins. Methods: Healthy 18–45-year-old adults received ChAd155-RSV, a placebo, or an active control (Bexsero) at Days (D) 0 and 30. An escalation from a low dose (5 × 10 9 viral particles) to a high dose (5 × 10 10 viral particles) occurred after the first 16 participants. Endpoints were solicited/unsolicited and serious adverse events (SAEs), biochemical/hematological parameters, cell-mediated immunogenicity by enzyme-linked immunospot, functional neutralizing antibodies, anti RSV-F immunoglobin (Ig) G, and ChAd155 neutralizing antibodies. Results: There were 7 participants who received the ChAd155-RSV low dose, 31 who received the ChAd155-RSV high dose, 19 who received the placebo, and 15 who received the active control. No dose-related toxicity or attributable SAEs at the 1-year follow-up were observed. The RSV-A neutralizing antibodies geometric mean titer ratios (post/pre-immunization) following a high dose were 2.6 (D30) and 2.3 (D60). The ratio of the fold-rise (D0 to D30) in anti-F IgG over the fold-rise in RSV-A–neutralizing antibodies was 1.01. At D7 after the high dose of the study vaccine, the median frequencies of circulating B-cells secreting anti-F antibodies were 133.3/10 6 (IgG) and 16.7/10 6 (IgA) in peripheral blood mononuclear cells (PBMCs). The median frequency of RSV-F–specific interferon γ–secreting T-cells after a ChAd155-RSV high dose was 108.3/10 6 PBMCs at D30, with no increase after the second dose. Conclusions: In adults previously naturally exposed to RSV, ChAd155-RSV generated increases in specific humoral and cellular immune responses without raising significant safety concerns. Clinical Trials Registration: NCT02491463. Abstract : We investigated the safety and immunogenicity of a novel chimpanzee-adenovirus-155 vaccine against respiratory syncytial virus (RSV; ChAd155-RSV). In healthy adults with previous natural RSV exposure, ChAd155-RSV generated antigen-specific humoral and cellular immune responses without raising significant safety concerns.